Invitro evaluation of Jholmal-3 of ageratina adenophora and artemisia myriantha leaves against pieris brassicae - Tashi Wangmo (CNR, Lobesa Tashi Wangmo, 2022)
includes acknowledgement and abstract
Keywords: Thesis